A Contested Identity: Contemporary Representation of Indonesian Chinese-Muslims on Instagram - Jesslyn Giovanni Mulyanto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
The existence of Chinese Muslims in Indonesia is surrounded by a heavily prejudiced belief that Chinese-ness and Islam are considered